Understanding the relationship between UK food-related obesity prevention policy and socioeconomic inequalities in obesity - Brown, Olivia (2024)
Background: Since 1992, 14 obesity prevention strategies for England have been published. Despite their publication obesity rates continue to rise and socioeconomic inequalities in obesity continue to widen. About two-thirds of adults in England are now classified as overweight or obese. Furthermore, adults living in the most deprived quintile of neighbourhoods are almost twice as likely to be obese as those living in the least deprived quintile of neighbourhoods. Among 10–11-year-olds and 4–5-year-olds, children in the most deprived areas are approximately twice as likely to be obese as their least deprived counterparts. 689 policies for obesity prevention have been proposed in prevention strategies for England. The most recent strategy was published in 2020, Tackling Obesity, indicating a new government commitment to tackling obesity and an acknowledgement of the importance of health inequalities related to obesity. This strategy proposed several flagship policies, including a restriction of the placement of high-fat, salt, and/or sugar (HFSS) products in stores’ prime locations. Over the past three decades, many of the proposed policies have been abandoned, delayed, or watered down. The legislation to restrict the placement of HFSS items in prime locations of stores in England came into force on October 1st 2022. This policy is explored in this thesis. Overall, there is a significant problem in the UK food policy landscape, where ample policies are proposed but few are implemented, and few target the structural drivers of obesity that are likely to have the most effective policy outcomes by favouring agentic policies. The food environment is central to obesity causation and prevention. Yet, obesity causation has frequently been attributed to individual behaviour, justifying the adoption of individual responsibility framing. Throughout the prevention strategies for England, there has been a preference of high agency policies. Agentic policies have been established to have lowest impact among the most deprived groups. Although the prevailing discourse on obesity continues to focus on individual responsibility and individual empowerment, there is growing recognition and uptake of structural policies that intend to influence the environment. Limited research has explored how recent prevention policies are perceived in terms of impact and effectiveness and how socioeconomic status may influence these perceptions. Additionally, exploring the perspectives and experiences of policy stakeholders within the obesity prevention policy process is uncommon, and is most often survey data, focused on specific policies or strategies or out of date. This PhD project offers the first study to investigate the impact of the legislation to restrict the placement of HFSS items in prime locations of stores in England. It is well established that the socioeconomic level of an environment influences the nature of the food environment. As a result, the outcomes of policies intended to influence the environment may differ. There is limited research addressing how policies intended to change the default environment may result in different outcomes determined by the socioeconomic status of an area. The overarching aim of this PhD project is to understand the relationship between foodrelated obesity prevention and inequalities in UK obesity rates. This overarching aim is underpinned by three core objectives: to understand UK-based adults’ experiences, attitudes, and future outlooks in relation to food-related obesity prevention policy; to explore how socioeconomic inequalities in obesity are considered in the obesity prevention policy process in the UK; and to investigate how the implementation of the restriction of the placement of HFSS products in stores’ prime locations influences the nature of the food environment. Methods: This thesis includes three studies: two sets of qualitative semi-structured interviews and an observational survey of the food retail environment in different socioeconomic areas of Nottinghamshire. The first study involves 31 semi-structured interviews with UK adults. The second study involves 14 semi-structured interviews with policy stakeholders, categorised into government officials, academics and knowledge brokers, and members of civil society and advocacy groups. Braun and Clarke’s thematic analysis was used for these studies. The third study is an observational survey of the food retail environment before and after the restriction of HFSS products in prime store locations. A total of 132 observations were conducted in supermarkets, chain convenience stores, and independent convenience stores in Nottinghamshire's highest and lowest socioeconomic areas. Products were classified by type, policy inclusion criteria, the Food Standards Agency’s Nutrient Profile Model’s Nutrient Profile Score, and Nova classification. Analysis includes descriptive statistics of the quantitative data from the observational survey, examining changes in product exposure in prime locations from 2022 to 2023 by the outlined classifications. Findings: Study 1: The main findings of this research reveals that UK adults view obesity as a major societal issue with multifaceted causes. Key themes include understanding obesity, nutritional literacy, experiences with the food environment, barriers and facilitators to maintaining a healthy weight, attitudes towards responsibility for obesity prevention, and perspectives on food policy. The most cited cause of obesity was the modern food environment's accessibility and affordability of unhealthy food. Maintaining a healthy weight in the UK is seen as unequal, with a healthy diet often considered a luxury. Lower socioeconomic groups face greater barriers, such as financial constraints and material conditions. Most participants believed responsibility for obesity prevention is shared between individuals and the government, but ultimately, individuals hold primary responsibility. Policies with the highest support were child-focused or involved educational or nudge-style approaches, with changing default environment policies favoured. However, participants expressed limited trust in government actions and doubted that obesity prevention policies would impact their lives. This perceived disconnect between the impact of obesity prevention policy and the participants’ lived experiences was most common among lower socioeconomic participants and higher weight classification participants. Study 2: In study two, the primary themes identified in study two were perceptions of obesity drivers in the UK, attitudes towards current and future obesity policies, barriers and facilitators to food policy implementation, considerations of inequalities in obesity prevention, and policy impact mechanisms. Stakeholders generally considered the food environment as the main cause of obesity in the UK, characterised by the high availability and affordability of energy-dense, nutrient-poor, ultra-processed foods, and the low availability and affordability of fresh products, especially in deprived urban areas. The food and drink industry's influence on the food environment was also highlighted. Stakeholders acknowledged progress in obesity policy but questioned its rate and sustainability, citing issues like policy proposal failures, silos, and loopholes as barriers to effectiveness. Key policy gaps, such as addressing weight stigma, were noted. Barriers to effective policy implementation included inconsistent government commitment, resistance to state intervention, and competing political priorities. Although stakeholders recognised the importance of addressing inequalities in obesity, most doubted the feasibility of targeting these inequalities due to the widespread prevalence of obesity and the limited impact of existing prevention policies. Many suggested adopting a health equity lens in policy design and implementation to better consider inequalities. Additionally, some stakeholders emphasised considering individual agency to understand its effect on intervention outcomes. The findings suggest that combining these approaches with population-level policies could more effectively address inequalities without specifically targeting them. Study 3: The third study found that restricting HFSS product placement from prime store locations reduced exposure to restricted products in supermarkets and chain convenience stores in both socioeconomic districts in Nottinghamshire. Exposure refers to a product's presence in prime store locations. The study observed significant adherence in supermarkets and chain convenience stores, with no notable change in independent convenience stores excluded from the policy. In supermarkets, across both socioeconomic areas exposure to products restricted by the policy was reduced from 39% of all exposures to 14%. In the chain convenience stores, the reduction in exposure was more than 26-percentage points in the lower socioeconomic area and more than 10-percentage points in the higher socioeconomic area. In comparison, the independent convenience stores that were not required to adhere to the policy, increased exposure of products restricted by the policy in the lower socioeconomic area by 8- percentage points. The policy also led to reduced exposure to high-sugar products such as treats and snacks. However, many restricted products remained in prime locations, indicating policy limitations. An unintended consequence of the policy was increased alcohol exposure, as evidenced by a 20-percentage point rise in alcohol exposure in supermarket checkout areas in both districts post-policy. This suggests alcohol products replaced removed items. Additionally, exposure to ultra-processed and less healthy items remained higher than exposure to restricted products due to exemption criteria. Conclusion: The research provides critical evidence on the link between food-related obesity prevention policies and obesity inequalities. The findings from two qualitative studies show that socioeconomic disparities in obesity are well-recognised among UK adults and policy stakeholders. It reveals that maintaining a healthy weight in the UK is unequally challenging, with barriers to healthy diets and weight being stronger among lower socioeconomic groups. Both studies described the food environment in lower socioeconomic areas as more obesogenic. This indicates the urgent need for equitable policy actions across all socioeconomic groups and values integrating lived experiences into policymaking. The research recommends including community voices in the policy process, bridging policy silos within food policy, and applying a health equity lens. Observations of the food environment show that policy can significantly shape exposures to unhealthy foods in retail environments, irrespective of socioeconomic status. However, the unintended rise in alcohol exposure due to restricting HFSS items highlights the need to consider bridging silos through including other unhealthy commodities in food policy design. Overall, the research emphasises the urgent need for action and the complex relationship between food-related obesity prevention policies and obesity inequalities. It suggests that existing policies are insufficient and perceived as failing to help the public maintain a healthy diet and weight in the modern food environment. The study highlights the challenge of prioritising inequalities amidst policy delays and shortcomings. It calls for moving inequalities to the centre of policymaking, building an evidence base on policy effectiveness among different social groups, incorporating a health equity lens, ensuring lived experiences inform policy development, and challenging assumptions about ‘normal’ environments and food behaviours for better future policy considerations.